The MC4 receptor agonist RO27‐3225 inhibits NLRP1‐dependent neuronal pyroptosis via the ASK1/JNK/p38 MAPK pathway in a mouse model of intracerebral haemorrhage. (9th April 2019) - Chen, Shengpan; Zuo, Yuchun; Huang, Lei; Sherchan, Prativa; Zhang, Jian; Yu, Zhengtao; Peng, Jianhua; Zhang, Junyi; Zhao, Lianhua; Doycheva, Desislava; Liu, Fei; Zhang, John H.; et al.
Abstract : Background and Purpose: Inflammasome‐mediated pyroptosis is an important neuronal cell death mechanism. Previous studies reported that activation of melanocortin MC4 receptor exerted neuroprotection in several neurological diseases. Here, we have investigated the role of MC4 receptor activation with RO27‐3225 in suppressing neuronal pyroptosis after experimental intracerebral haemorrhage (ICH) and the underlying mechanism. Experimental Approach: One hundred and sixty‐nine male CD1 mice were used. ICH was induced by injection of bacterial collagenase into the right‐side basal ganglia. RO27‐3225, a selective agonist of MC4 receptor, was injected intraperitoneally at 1 hr after ICH. To elucidate the underlying mechanism, we used the specific MC4 receptor antagonist HS024 and NQDI‐1, a specific inhibitor of the apoptosis signalling‐regulating kinase 1 (ASK1). Neurological tests, Western blot, Fluoro‐Jade C, TUNEL, and immunofluorescence staining were conducted. Key Results: Expression of MC4 receptor and the NOD‐like receptor family, pyrin domain containing 1 (NLRP1) inflammasome in brain were increased after ICH. RO27‐3225 treatment decreased neuronal pyroptosis and neurobehavioural deficits at 24 and 72 hr after ICH. RO27‐3225 reduced the expression of p‐ASK1, p‐JNK, p‐p38 MAPK, NLRP1 inflammasome, cleaved caspase‐1, and IL‐1β after ICH. HS024 pretreatment prevented the effects of RO27‐3225. Similar to RO27‐3225, NQDI‐1 alone improved neurological functions and down‐regulated ASK1/JNK/p38MAPK expression after ICH. Conclusions and Implications: RO27‐3225 suppressed NLRP1‐dependent neuronal pyroptosis and improved neurological function, possibly mediated by activation of MC4 receptor and inhibition of ASK1/JNK/p38 MAPK signalling pathways, after experimental ICH in mice. The MC4 receptor may be a promising therapeutic target for the management of ICH.